2020
DOI: 10.1128/mra.00179-20
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Human Immunodeficiency Virus Type 1 Sequence in J-Lat 10.6

Abstract: The full length of HIV/R7/E−/GFP integrated in the J-Lat 10.6 cell line was sequenced in this study. The single copy of the integrated virus, including the breakpoints from the human chromosome to the provirus, was amplified by two separate PCRs. A 10,200-bp genome sequence was acquired, analyzed, and deposited in GenBank.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…a PCS: Predicted cleavage sites; b HXB2: Whether the absolute gRNA sequence perfectly matched with HXB2 reference sequence. Note that the NL4-3 and R7/E-/eGFP in J-Lat (Chung C.-H. et al, 2020b) also showed the same results as HXB2 (Table S1); c# OT: number of potential off-target sites with CFD above 0.569 in human genome. d g8D9BC2: Previously published as gTatRev in (Wang et al, 2016a;Wang et al, 2016b;Darcis et al, 2019); e g01A4C4: Previously published as gGag3 in (Wang et al, 2016a;Zhao et al, 2017).…”
Section: Low Diversity Target Sites With High Global Patient Coveragementioning
confidence: 61%
“…a PCS: Predicted cleavage sites; b HXB2: Whether the absolute gRNA sequence perfectly matched with HXB2 reference sequence. Note that the NL4-3 and R7/E-/eGFP in J-Lat (Chung C.-H. et al, 2020b) also showed the same results as HXB2 (Table S1); c# OT: number of potential off-target sites with CFD above 0.569 in human genome. d g8D9BC2: Previously published as gTatRev in (Wang et al, 2016a;Wang et al, 2016b;Darcis et al, 2019); e g01A4C4: Previously published as gGag3 in (Wang et al, 2016a;Zhao et al, 2017).…”
Section: Low Diversity Target Sites With High Global Patient Coveragementioning
confidence: 61%
“…To assess the extent of nucleotide misincorporation (polymerase errors) that may occur during the PRLS assay, we activated J-Lat 10.3 cells ( 40 ) with phorbol 12-myristate 13-acetate (PMA) and extracted the supernatant before amplifying the cDNA with the gag -3′ primers. We compared 94 individual gag -3′ sequences (828,705 total nucleotides) to the published sequence of the proviral genome found in J-Lat cells ( 41 ) and determined the overall error rate of the assay per nucleotide to be 0.0076% (95% confidence interval [CI], 0.0054%, 0.0098%), or approximately 0.63 nucleotides/ gag -3′ genome.…”
Section: Resultsmentioning
confidence: 99%
“…Latency reversal was induced by incubating 5 × 10 4 cells with 2 ng/mL phorbol 12-myristate 13-acetate (PMA) for 48 h. The culture supernatant from the activated cells was harvested and stored at −80°C until used for RNA extraction. Following RNA extraction and cDNA synthesis, 94 genomes were amplified and sequenced using the PRLS assay, and SNPs or frameshift mutations were identified in the genomes that were genetically different from the reference sequence for the J-Lat cell line ( 41 ). The number of nucleotides involved in these changes was quantified and divided by the total number of nucleotides sequenced (828,705 total nucleotides) to determine the mean and 95% CI for the error rate of the assay.…”
Section: Methodsmentioning
confidence: 99%
“…To construct a reference reflecting integration of HIV-1 into J-Lat cells, we started with the UCSC hg38 human reference sequence from the Illumina iGenomes collection (https://support.illumina.com/sequencing/sequencing_software/igenome.html). Sequence for the integrated HIV-1 genome, including flanking human sequence, was obtained from accession MN989412.1 [84]. Accounting for flanking human sequence, we excised chr9:136468439-136468594 from the reference Fasta file and inserted MN989412.1 in its place.…”
Section: Methodsmentioning
confidence: 99%
“…Sequence for the integrated HIV-1 genome, including flanking human sequence, was obtained from accession MN989412.1 [78]. Accounting for flanking human sequence, we excised chr9:136468439-136468594 from the reference Fasta file and inserted MN989412.1 in its place.…”
Section: Automated Cutandtag Profilingmentioning
confidence: 99%